'Analysing a parent's capacity to change: towards a model for child protection social workers'. Issue 3 (3rd July 2021) - Houston, Stan; Swords, Calvin
ABSTRACT: In cases where child protection concerns are evident, a central query within inter-professional, safeguarding assessments, centres on the parents' capacity to change to enhance their child's lived experience. Social workers, as key professionals co-ordinating such assessments, require analytical tools and models to enable them and others to reach a considered judgement on this pressing, complex aspect of case inquiry. This article describes one such model. The model builds on the C-Change Approach which reviews the change process from a mainly cognitive-behavioural perspective. While recognising the strengths of this contribution to child protection assessment, the authors have extended it by examining change from a psycho-dynamic orientation. This orientation takes account, not only of the intra-psychic dynamics within the individual, but also the relational forces at work between people. Lastly, the authors consider how this extended model can be utilised to analyse and facilitate desired changes in parenting practices. Here, they draw on the helpful notion of a force-field analysis: a conceptual representation of the dynamics of change within a social situation.